Silicon oxide high-barrier film composite packaging bag and preparation method thereof
By adopting a multi-layer structure of silicon oxide high-barrier film composite packaging bag in the packaging bag, combining polyphenylene sulfide, boron nitride nanosheets, silicon oxide/boron nitride composite film and polylactate nanofiber filament blend materials, the problem of insufficient barrier performance of traditional packaging bags is solved, and efficient gas barrier and various performance improvements are achieved.
Patent Information
- Application Number
- CN202411749789.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
When traditional packaging bags face products that require long-term storage and are sensitive to oxygen and moisture, their barrier properties seem to be unscrupulous, and new high-barrier materials such as silicon oxide and boron nitride have problems such as difficult processing and high cost.
The silicon oxide high-barrier film composite packaging bag adopting a multi-layer structure, including the outer polyphenylene sulfide (PPS) material, the intermediate boron nitride (BN) nanosheet dispersion-enhanced polyimide (PI) layer, the core layer silicon oxide ()/boron nitride (BN) composite barrier film, and the inner layer of polylactic acid (PLA) and cellulose nanofiber filaments (CNF). The layers are closely combined with each layer through atomic layer deposition (ALD) technology and hot pressing technology to form a multiple barrier barrier.
It achieves efficient gas barrier, extends the shelf life of the products in the packaging, and has good heat resistance, chemical corrosion resistance, mechanical strength and biocompatibility, low cost and easy to prepare.
Smart Images

Figure CN119502520A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging bags, in particular to a silicon oxide high-barrier film composite packaging bag and a preparation method thereof. Background Art
[0002] With the development of modern packaging technology, the performance requirements for packaging bags are increasing, especially in the field of food and pharmaceutical packaging, which requires packaging bags to have high barrier properties, heat resistance, chemical corrosion resistance and good mechanical strength. Although traditional packaging bag materials, such as polyethylene (PE) and polypropylene (PP), meet basic packaging needs to a certain extent, their barrier properties are insufficient when facing products that need to be stored for a long time and are sensitive to oxygen and moisture.
[0003] To overcome this defect, the industry has begun to explore the use of new high-barrier materials, such as silicon oxide ( ) and boron nitride (BN). These materials have excellent barrier properties and thermal stability, but when used alone, they often have problems such as difficulty in processing and high cost. Therefore, how to develop a composite packaging bag with high barrier properties, good processing performance and cost-effectiveness through reasonable material combination and structural design has become a research hotspot in the current packaging technology field. For this purpose, a silicon oxide high barrier film composite packaging bag and its preparation method are proposed. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a silicon oxide high-barrier film composite packaging bag and a preparation method thereof to solve the background technical problems.
[0005] In the first aspect, to achieve the above-mentioned purpose, the present invention provides the following technical solutions: a silicon oxide high barrier film composite packaging bag, comprising an outer layer, an intermediate layer, a core layer and an inner layer arranged in sequence, wherein the materials used meet the standards of food safety and drug safety, specifically: Outer layer: Made of polyphenylene sulfide (PPS) material with a thickness of 80 to 120 microns.
[0006] Middle layer: It is a polyimide (PI) layer reinforced by boron nitride (BN) nanosheet dispersion with a thickness of 20 to 40 microns; BN nanosheets are evenly dispersed in the PI matrix through ultrasonic dispersion technology to form an effective gas barrier, which is then coated on the polyethylene terephthalate (PET) substrate by coating.
[0007] Core layer: silicon oxide ( ) / boron nitride (BN) composite barrier film, alternately deposited on the intermediate layer by atomic layer deposition (ALD) technology and BN layers, forming a multi-layer alternating structure with a total thickness of 150 to 300 nanometers.
[0008] Inner layer: A blend of polylactic acid (PLA) and cellulose nanofibrils (CNF) with a thickness of 30 to 60 microns, evenly coated on the core layer.
[0009] Preferably, the thickness of the outer layer of polyphenylene sulfide (PPS) material is further limited to 100 microns (to optimize mechanical strength and processing performance while maintaining good heat resistance and chemical corrosion resistance).
[0010] Preferably, in the intermediate layer of polyimide (PI) layer reinforced with boron nitride (BN) nanosheet dispersion, the content of BN nanosheets accounts for 5% to 15% of the weight of the PI matrix (so as to significantly improve the gas barrier properties and thermal stability without affecting the performance of the PI matrix).
[0011] Preferably, the core layer silicon oxide ( The number of alternating deposition layers of the composite barrier film of boron nitride (BN) is 5 to 20 layers, each layer and BN thickness is controlled between 5 and 15 nm (to achieve finer interlayer control and lower gas permeability).
[0012] Preferably, in the blended material of the inner layer of polylactic acid (PLA) and cellulose nanofibrils (CNF), the content of CNF accounts for 1% to 10% of the weight of PLA (to enhance the mechanical properties and barrier properties of the inner layer while maintaining the biocompatibility and degradability of PLA).
[0013] In a second aspect, a method for preparing a silicon oxide high barrier film composite packaging bag comprises the silicon oxide high barrier film composite packaging bag described in any one of the first aspects, comprising the following detailed preparation steps: Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 100 microns, clean the surface, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0014] PI intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a 10% PI solution. BN nanosheets were dispersed in another DMF solvent at a ratio of 0.5% to 2%, and ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure uniform dispersion of BN nanosheets in the solvent.
[0015] PET substrate: A PET film with a thickness of 125 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0016] PLA / CNF inner layer material: PLA resin is mixed with CNF in a ratio of 5% to 10%, and the blending is carried out at a temperature of 180°C to 220°C through melt blending technology to ensure uniform dispersion of CNF in the PLA matrix.
[0017] Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 1:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 20 to 40 μm.
[0018] The drying process is performed at a temperature of 80°C to 120°C for 2 to 4 hours to remove the solvent and form a BN nanosheet-reinforced PI interlayer.
[0019] The curing process is carried out at a temperature of 150°C to 200°C for 1 to 2 hours to improve the stability and adhesion of the intermediate layer.
[0020] Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition is performed on the pre-treated PI intermediate layer. and a BN layer; the deposition temperature is 200°C to 300°C, and the deposition pressure is 0.1 to 1 Torr.
[0021] After each layer is deposited, a short annealing treatment is performed at a temperature of 300°C to 400°C for 5 to 15 minutes to eliminate internal stress and improve the density and stability of the film.
[0022] Step 4: Inner layer preparation The pretreated PLA / CNF blended material is evenly coated on the core layer by melt extrusion technology, the extrusion temperature is 200°C to 240°C, and the coating thickness is 30 to 60 microns.
[0023] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0024] Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 150°C to 200°C, the pressure being 5 to 10MPa, and the time being 1 to 2 minutes.
[0025] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0026] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0027] Preferably, in step three: Deposition When depositing the SiO2 layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse and an inert gas purge.
[0028] When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses polyimide (PI), silicon oxide ( ) / boron nitride (BN) composite barrier film and the blended material of polylactic acid (PLA) and cellulose nanofibrils (CNF) form a multiple barrier barrier, which effectively reduces the permeability of gases such as oxygen and moisture, and extends the shelf life of the products in the package. At the same time, the composite material is low in cost and easy to prepare.
[0030] 2. The PPS material used in the outer layer of the present invention has good heat resistance and chemical corrosion resistance, and can maintain the integrity of the packaging bag in high temperature and harsh chemical environments, further broadening the application range of the packaging bag.
[0031] 3. The blended material of polylactic acid (PLA) and cellulose nanofibrils (CNF) used in the inner layer of the present invention not only enhances the mechanical properties and barrier properties of the inner layer, but also gives the packaging bag good biocompatibility and degradability, which is in line with the current trend of environmental protection and sustainable development.
[0032] 4. The high barrier film composite packaging bag of the present invention has excellent performance in barrier properties, heat resistance, chemical corrosion resistance, mechanical strength and biocompatibility, so it is suitable for packaging of various products such as food, medicine, chemicals, etc., and has broad market prospects.
[0033] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the structure of the silicon oxide high barrier film composite packaging bag of the present invention; Figure 2 It is a schematic diagram of the structure of the present invention; Figure 3The present invention is a flow chart for preparing the silicon oxide high barrier film composite packaging bag. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this technical field without creative work are within the scope of protection of the present invention.
[0036] See also Figure 1-3 The present invention provides a silicon oxide high barrier film composite packaging bag, comprising an outer layer, an intermediate layer, a core layer and an inner layer arranged in sequence, specifically: Outer layer: Made of polyphenylene sulfide (PPS) material with a thickness of 80 to 120 microns.
[0037] Middle layer: It is a polyimide (PI) layer reinforced by boron nitride (BN) nanosheet dispersion with a thickness of 20 to 40 microns; BN nanosheets are evenly dispersed in the PI matrix through ultrasonic dispersion technology to form an effective gas barrier, which is then coated on the polyethylene terephthalate (PET) substrate by coating.
[0038] Core layer: silicon oxide ( ) / boron nitride (BN) composite barrier film, alternately deposited on the intermediate layer by atomic layer deposition (ALD) technology and BN layers, forming a multi-layer alternating structure with a total thickness of 150 to 300 nanometers.
[0039] Inner layer: A blend of polylactic acid (PLA) and cellulose nanofibrils (CNF) with a thickness of 30 to 60 microns, evenly coated on the core layer.
[0040] The materials used meet the standards of food safety and drug safety.
[0041] The specific preparation method is: Embodiment 1:
[0042] Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 100 microns, clean the surface, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0043] PI intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a 10% PI solution. BN nanosheets were dispersed in another portion of DMF solvent at a ratio of 2%, and ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure uniform dispersion of BN nanosheets in the solvent.
[0044] PET substrate: A PET film with a thickness of 125 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0045] PLA / CNF inner layer material: PLA resin was mixed with CNF at a ratio of 8%, and the blending was carried out at a temperature of 200°C through melt blending technology to ensure the uniform dispersion of CNF in the PLA matrix.
[0046] Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 1:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 30 μm.
[0047] The drying process was carried out at 80 °C for 4 h to remove the solvent and form a BN nanosheet-reinforced PI interlayer.
[0048] Curing was performed at 150°C for 2 hours to improve the stability and adhesion of the intermediate layer.
[0049] Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, SiO2 and BN layers are alternately deposited on the pre-treated PI interlayer; the deposition temperature is 200°C and the deposition pressure is 0.1 to 1 Torr.
[0050] After each layer is deposited, a short annealing treatment is performed at 300° for 15 minutes to eliminate internal stress and improve the density and stability of the film.
[0051] Deposition When depositing the SiO2 layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse and an inert gas purge.
[0052] When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
[0053] Step 4: Inner layer preparation The pretreated PLA / CNF blended material was evenly coated on the core layer by melt extrusion technology, the extrusion temperature was 200°C, and the coating thickness was 60 μm.
[0054] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0055] Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 150°C, the pressure being 10MPa and the time being 2 minutes.
[0056] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0057] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0058] Embodiment 2:
[0059] Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 120 microns, clean the surface, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0060] PI intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a PI solution with a concentration of 8%. BN nanosheets were dispersed in another portion of DMF solvent at a ratio of %. Ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure that the BN nanosheets were evenly dispersed in the solvent.
[0061] PET substrate: A PET film with a thickness of 110 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0062] PLA / CNF inner layer material: PLA resin and CNF were mixed at a ratio of 10% and blended at 220°C by melt blending technology to ensure uniform dispersion of CNF in the PLA matrix.
[0063] Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 2:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 40 μm.
[0064] The solvent was removed by drying at 120 °C for 2 h to form a BN nanosheet-reinforced PI interlayer.
[0065] Curing was performed at 200°C for 1 hour to improve the stability and adhesion of the intermediate layer.
[0066] Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition is performed on the pre-treated PI intermediate layer. and BN layers; the deposition temperature is 300°C and the deposition pressure is 0.5 to 1 Torr.
[0067] After each layer is deposited, a short annealing treatment is performed at 400° for 5 minutes to eliminate internal stress and improve the density and stability of the film.
[0068] Deposition When depositing the SiO2 layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse and an inert gas purge.
[0069] When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
[0070] Step 4: Inner layer preparation The pretreated PLA / CNF blended material was evenly coated on the core layer by melt extrusion technology, with an extrusion temperature of 150°C and a coating thickness of 30 μm.
[0071] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0072] Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 200°C, the pressure being 8MPa and the time being 1 minute.
[0073] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0074] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0075] Embodiment three:
[0076] Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 80 microns, perform surface cleaning, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0077] PI intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a 10% PI solution. BN nanosheets were dispersed in another portion of DMF solvent at a ratio of 0.5%, and ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure uniform dispersion of BN nanosheets in the solvent.
[0078] PET substrate: A PET film with a thickness of 100 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0079] PLA / CNF inner layer material: PLA resin was mixed with CNF at a ratio of 5%, and the blending was carried out at a temperature of 180°C through melt blending technology to ensure the uniform dispersion of CNF in the PLA matrix.
[0080] Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 1.5:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 20 μm.
[0081] The solvent was removed by drying at 100 °C for 3 h to form a BN nanosheet-reinforced PI interlayer.
[0082] Curing was performed at 100°C for 1.5 hours to improve the stability and adhesion of the intermediate layer.
[0083] Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition is performed on the pre-treated PI intermediate layer. and BN layer; the deposition temperature is 150°C, and the deposition pressure is 0.8 to 1 Torr.
[0084] After each layer is deposited, a short annealing treatment is performed at 350° for 10 min to eliminate internal stress and improve the density and stability of the film.
[0085] Deposition When depositing the SiO2 layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse and an inert gas purge.
[0086] When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
[0087] Step 4: Inner layer preparation The pretreated PLA / CNF blended material was evenly coated on the core layer by melt extrusion technology, with an extrusion temperature of 220°C and a coating thickness of 40 μm.
[0088] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0089] Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 180°C, the pressure being 8MPa and the time being 1.5 minutes.
[0090] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0091] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0092] Comparative Example 1:
[0093] Step 1: Material preparation and pretreatment Outer material: Select a polypropylene (PP) film with a thickness of 200 microns, clean the surface, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0094] PET substrate: A PET film with a thickness of 100 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0095] PLA / CNF inner layer material: PLA resin was mixed with CNF at a ratio of 5%, and the blending was carried out at a temperature of 180°C through melt blending technology to ensure the uniform dispersion of CNF in the PLA matrix.
[0096] Step 2: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition on PET substrate and BN layer; the deposition temperature is 200°C to 300°C, and the deposition pressure is 0.1 to 1 Torr.
[0097] Deposition When depositing the SiO2 layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse and an inert gas purge.
[0098] When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
[0099] Step 3: Inner layer preparation The pretreated PLA / CNF blended material was evenly coated on the core layer by melt extrusion technology, with an extrusion temperature of 220°C and a coating thickness of 40 μm.
[0100] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0101] Step 4: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 180°C, the pressure being 8MPa and the time being 1.5 minutes.
[0102] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0103] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0104] Comparative Example 2:
[0105] Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 80 microns, perform surface cleaning, and wipe the surface with ethanol solution to remove dust, grease and impurities.
[0106] Intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a 10% PI solution. BN nanosheets were dispersed in another portion of DMF solvent at a ratio of 0.5%, and ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure uniform dispersion of BN nanosheets in the solvent.
[0107] PET substrate: A PET film with a thickness of 100 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers.
[0108] PLA / CNF inner layer material: PLA resin was mixed with CNF at a ratio of 5%, and the blending was carried out at a temperature of 180°C through melt blending technology to ensure the uniform dispersion of CNF in the PLA matrix.
[0109] Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 1.5:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 20 μm.
[0110] The solvent was removed by drying at 100 °C for 3 h to form a BN nanosheet-reinforced PI interlayer.
[0111] Curing was performed at 100°C for 1.5 hours to improve the stability and adhesion of the intermediate layer.
[0112] Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition is performed on the pre-treated PI intermediate layer. and ; The deposition temperature is 200°C to 300°C, and the deposition pressure is 0.1 to 1Torr.
[0113] After each layer is deposited, a short annealing treatment is performed at a temperature of 300°C to 400°C for 5 to 15 minutes to eliminate internal stress and improve the density and stability of the film.
[0114] Step 4: Inner layer preparation The pretreated PLA / CNF blended material was evenly coated on the core layer by melt extrusion technology, with an extrusion temperature of 220°C and a coating thickness of 40 μm.
[0115] The film was cooled and solidified at room temperature for 24 hours to form an inner layer.
[0116] Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, with the hot pressing temperature being 180°C, the pressure being 8MPa and the time being 1.5 minutes.
[0117] Finished products are quality checked, including testing for thickness, uniformity, barrier properties and mechanical strength.
[0118] According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
[0119] Test example:
[0120] This test example provides performance tests and test results of packaging bags prepared in Examples 1-3 and Comparative Examples 1 and 2; The prepared packaging bags were tested using an infrared water vapor transmission rate tester and the experimental results are shown in Table 1; Table 1 shows the barrier effects of the packaging bags obtained in Examples 1-3 and Comparative Examples 1 and 3:
[0121] First, by comparing Comparative Example 1 and Example 1, it is found that Comparative Example 1 does not use a PI intermediate layer substrate, while Example 1 uses a PI intermediate layer substrate. The experimental results show that the barrier effect of Example 1 is better than that of Comparative Example 1. This is mainly due to the fact that the PI intermediate layer substrate can form an effective gas barrier while improving the overall mechanical properties and thermal stability.
[0122] Secondly, by comparing Example 2 with Example 2, it can be found that the core layers of the two are different. The experimental results show that the barrier effect of Example 2 is better than that of Example 2, which is mainly due to the fact that the core layer of Example 2 adopts and BN layers are deposited alternately, while Comparative Example 2 uses and alternating deposition and BN have advantages over alternate deposition and , and BN is more stable at high temperatures.
[0123] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A silicon oxide high barrier film composite packaging bag, characterized in that: It includes an outer layer, a middle layer, a core layer and an inner layer arranged in sequence, and the materials used are all in accordance with the standards of food safety and drug safety, specifically: Outer layer: Made of polyphenylene sulfide (PPS) material, with a thickness of 80 to 120 microns; Middle layer: a polyimide (PI) layer reinforced by boron nitride (BN) nanosheet dispersion, with a thickness of 20 to 40 microns; BN nanosheets are evenly dispersed in the PI matrix by ultrasonic dispersion technology to form an effective gas barrier, which is then coated on the polyethylene terephthalate (PET) substrate by coating; Core layer: Silicon oxide ( ) / boron nitride (BN) composite barrier film, alternately deposited on the intermediate layer by atomic layer deposition (ALD) technology and BN layers, forming a multi-layer alternating structure with a total thickness of 150 to 300 nm; Inner layer: A blend of polylactic acid (PLA) and cellulose nanofibrils (CNF) with a thickness of 30 to 60 microns, evenly coated on the core layer.
2. The silicon oxide high barrier film composite packaging bag according to claim 1, characterized in that: The thickness of the outer layer polyphenylene sulfide (PPS) material is further limited to 100 microns (to optimize mechanical strength and processing performance while maintaining good heat resistance and chemical corrosion resistance).
3. The silicon oxide high barrier film composite packaging bag according to claim 1, characterized in that: In the intermediate layer of polyimide (PI) layer reinforced by boron nitride (BN) nanosheet dispersion, the content of BN nanosheets accounts for 5% to 15% of the weight of the PI matrix (so as to significantly improve the gas barrier performance and thermal stability without affecting the performance of the PI matrix).
4. The silicon oxide high barrier film composite packaging bag according to claim 1, characterized in that: The core layer silicon oxide ( The number of alternating deposition layers of the composite barrier film of boron nitride (BN) is 5 to 20 layers, each layer and BN thickness is controlled between 5 and 15 nm (to achieve finer interlayer control and lower gas permeability).
5. The silicon oxide high barrier film composite packaging bag according to claim 1, characterized in that: In the blended material of the inner layer of polylactic acid (PLA) and cellulose nanofibrils (CNF), the content of CNF accounts for 1% to 10% of the weight of PLA (to enhance the mechanical properties and barrier properties of the inner layer while maintaining the biocompatibility and degradability of PLA).
6. A method for preparing a silicon oxide high barrier film composite packaging bag, comprising the silicon oxide high barrier film composite packaging bag according to any one of claims 1 to 5, characterized in that: The detailed preparation steps include: Step 1: Material preparation and pretreatment PPS outer layer material: Select a PPS film with a thickness of 100 microns, clean the surface, and wipe the surface with ethanol solution to remove dust, grease and impurities; PI intermediate layer substrate: PI resin was dissolved in dimethylformamide (DMF) solvent to form a 10% PI solution. BN nanosheets were dispersed in another portion of DMF solvent at a ratio of 0.5% to 2%, and ultrasonic treatment was performed for 30 minutes and high-speed stirring was performed for 1 hour to ensure uniform dispersion of BN nanosheets in the solvent; PET substrate: A PET film with a thickness of 125 μm was selected and subjected to surface plasma treatment for 2 minutes at a power of 50 W to improve adhesion with subsequent deposited layers; PLA / CNF inner layer material: PLA resin and CNF are mixed in a ratio of 5% to 10%, and the blending is carried out at a temperature of 180°C to 220°C through melt blending technology to ensure uniform dispersion of CNF in the PLA matrix; Step 2: Preparation of the middle layer The pretreated PI solution and the BN nanosheet dispersion were mixed in a ratio of 1:1, and the mixture was evenly coated on the pretreated PET substrate by blade coating with a coating thickness of 20 to 40 μm; Performing a drying process at a temperature of 80°C to 120°C for 2 to 4 hours to remove the solvent and form a PI intermediate layer reinforced by BN nanosheets; Curing is performed at a temperature of 150°C to 200°C for 1 to 2 hours to improve the stability and adhesion of the intermediate layer; Step 3: Core layer preparation Using atomic layer deposition (ALD) technology, alternate deposition is performed on the pre-treated PI intermediate layer. and a BN layer; a deposition temperature of 200°C to 300°C and a deposition pressure of 0.1 to 1 Torr; After each layer is deposited, a short annealing treatment is performed at a temperature of 300°C to 400°C for 5 to 15 minutes to eliminate internal stress and improve the density and stability of the film; Step 4: Inner layer preparation The pretreated PLA / CNF blend material is uniformly coated on the core layer by melt extrusion technology, the extrusion temperature is 200°C to 240°C, and the coating thickness is 30 to 60 microns; Perform cooling and curing treatment at room temperature for 24 hours to form an inner layer; Step 5: Lamination and post-processing The outer PPS film, the middle layer, the core layer and the inner layer are tightly combined together by hot pressing technology, the hot pressing temperature is 150°C to 200°C, the pressure is 5 to 10MPa, and the time is 1 to 2 minutes; Conduct quality checks on finished products, including testing for thickness, uniformity, barrier properties and mechanical strength; According to the needs, subsequent processing such as cutting, printing and sealing can be carried out.
7. The method for preparing a silicon oxide high barrier film composite packaging bag according to claim 6, characterized in that: In step three: Deposition When depositing the layer, tetraethylsilane was introduced as the silicon source and water vapor was used as the oxidant. The deposition cycle was 50 to 100 cycles, and each cycle included a silicon source pulse, an oxidant pulse, and an inert gas purge. When depositing the BN layer, trimethylboron is introduced as a boron source and ammonia is used as a nitrogen source. The deposition cycle is 50 to 100 cycles, and each cycle includes a boron source pulse, a nitrogen source pulse, and an inert gas purge.
Citation Information
Patent Citations
Polymer material with continuously-alternating layer structure and preparation method for same
CN103481393A
Barrier composite film and preparation method thereof
CN110387195A
PLA (polylactic acid) barrier film with multiple stereo crystal layers and preparation method of PLA barrier film
CN118085697A
Degradable nanocellulose composite packaging material and preparation method thereof
CN118725531A
Gas barrier package bag and production method of gas barrier package body using the same
JP2014061682A